Who Cares about Relative Deprivation? - Ravallion, Martin; Lokshin, Michael (2012)
If relative deprivation matters to welfare in poor countries as much as it apparently does in rich ones then one would have to question the priority given to economic growth over redistribution in current development policies. We look for evidence in one of the world's poorest countries, Malawi. Using new survey questions that help address likely biases in past tests, we find that relative deprivation is not the dominant concern for most of our sample, although it is for the comparatively well off, including in urban areas. Our results strengthen the welfarist case for a policy focus on absolute levels of living in poor countries. The pattern of externalities suggests that there will be too much poverty and inequality from the point of view of aggregate efficiency.